2017
DOI: 10.1016/j.brs.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transcranial direct current stimulation over primary motor cortex (anode) and contralateral supraorbital area (cathode) on clinical pain severity and mobility performance in persons with knee osteoarthritis: An experimenter- and participant-blinded, randomized, sham-controlled pilot clinical study

Abstract: Background Previous studies indicate that transcranial direct current stimulation (tDCS) with anode over motor cortex (M1) and cathode over contralateral supraorbital region (SO) may be effective in reducing pain, but these studies are limited in number and have not focused on older adults with osteoarthritis (OA). Objective To evaluate the preliminary efficacy and safety of M1-SO applied tDCS on clinical pain severity and mobility performance in adults with knee OA pain. Methods Forty 50- to 70-year-old c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(136 citation statements)
references
References 51 publications
12
124
0
Order By: Relevance
“…This suggests activation of the opioid system, in part, mediates the analgesic effects of primary motor cortex tDCS and others have shown the release of opioids in the midbrain in both healthy subjects (Dossantos et al, 2014) and during chronic pain (Dossantos et al, 2012). Similar clinical pain-relieving effects have been seen in elderly patients with chronic musculoskeletal pain (Ahn et al, 2017;Harvey et al, 2017), small-fibre neuropathy (Kim et al, 2013) and in patients with chronic visceral pain (Volz et al, 2016). Further positive results have demonstrated that primary motor cortex stimulation may provide an effective treatment in drug-resistant neuropathic pain conditions; showing analgesic effects in phantom limb pain (Bolognini et al, 2015) and trigeminal neuralgia (Hagenacker et al, 2014).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This suggests activation of the opioid system, in part, mediates the analgesic effects of primary motor cortex tDCS and others have shown the release of opioids in the midbrain in both healthy subjects (Dossantos et al, 2014) and during chronic pain (Dossantos et al, 2012). Similar clinical pain-relieving effects have been seen in elderly patients with chronic musculoskeletal pain (Ahn et al, 2017;Harvey et al, 2017), small-fibre neuropathy (Kim et al, 2013) and in patients with chronic visceral pain (Volz et al, 2016). Further positive results have demonstrated that primary motor cortex stimulation may provide an effective treatment in drug-resistant neuropathic pain conditions; showing analgesic effects in phantom limb pain (Bolognini et al, 2015) and trigeminal neuralgia (Hagenacker et al, 2014).…”
Section: Discussionmentioning
confidence: 71%
“…They may also provide insight into the efficacy of tDCS in both clinical and nonclinical settings. There is a growing body of evidence that suggests tDCS is more effective in patients with chronic pain Borckardt et al, 2011Borckardt et al, , 2017Jurgens et al, 2012;Kim et al, 2013;Hagenacker et al, 2014;Bolognini et al, 2015;Volz et al, 2016;Ahn et al, 2017;Harvey et al, 2017;Khedr et al, 2017a) compared to studies that have attempted to dissect the analgesic mechanisms in healthy subjects (Boggio et al, 2008;Csifcsak et al, 2009;Hansen et al, 2011;Jurgens et al, 2012;Aslaksen et al, 2014;Ihle et al, 2014). These lines of evidence have now not only shown a reduction in pain intensity in chronic pain patients, but also distinct changes in the brain regions involved in the top-down modulation of pain processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons with OA are reported to display higher experimental pain sensitivity, such as lower heat pain thresholds and tolerances, lower pressure pain threshold (PPT), and higher punctate mechanical pain. 6 , 18 , 19 However, previous studies, including ours, examined clinical outcomes associated with tDCS, 11 , 13 , 20 , 21 but few studies reported changes in experimental pain sensitivity after tDCS. The examination of the effect of tDCS on experimental pain sensitivity, which can be different based on the parameters of tDCS (eg, polarity, electric current intensity, and target site), could help clinicians and researchers to better understand the underlying mechanisms of action involved with tDCS and the role played by the cortex in the integration of nociceptive information.…”
Section: Introductionmentioning
confidence: 79%
“…Thus, while evidence supports combined interventions for thumb OA, we are unable to make specific recommendations regarding combined interventions for knee OA, or for other affected joints. With respect to adjunct interventions, we found evidence to support the use of tape for knee OA 21,55,57 , assistive devices for hand OA 59 , thumb splints for thumb OA 60 , manual therapy for knee OA 23,45,47,53 and neck OA 65 , acupuncture for knee OA 44 , and electrophysical agents for knee OA 19,22,48 (Tables III and IV), while conflicting evidence was found for transcranial direct current stimulation (tDCS) 30,37 (Table IV). Taken together with established clinical guidelines, our findings reinforce that these interventions should be adjuncts to accompany core recommended interventions for OA, rather than be used as standalone or key treatments 2,3,9e16 .…”
Section: Discussionmentioning
confidence: 99%